PENGAPLIKASIAN MODEL KOOPERATIF PADA PEMBELAJARAN MATEMATIKA KELAS IV DI SDIT AL-FURQAN - Dewi, Ratih Puspita; Mahmudah, Istiyati (Universitas Tanjungpura, 2024)
Education has meaning as an undertaking to enlighten nations. In addition, education also has achievement to increasing on the quality of people in Indonesia. Math learning is one of essential subject in education with the purpose of increasing students' intelligence. In the study of mathematics, students can think critically and be skilled in calculating and also have the ability to implement the basic mathematical concepts in lessons. The purpose of this study is to analyze cooperative application on mathematics of fourth grade at SDIT Al-Furqan Palangka Raya. The method of this study was a descriptive method, which meant the researchers' results were transmitted and explained in words was also presented by a literature review/study literature. The finding showed that application of the cooperative learning model at SDIT Al-Furqan Palangka Raya is said to be appropriate and is able to help students to understand a learning material well. In this way, this cooperative learning model is able to increase the knowledge of students in the process of understanding a concept and the results of students